The Effect of Green Innovation, Carbon Emission Disclosure, And Environmental Costs on Company Value with Industry Type as A Moderation Variable - AMBARWATI AKIB (International Journal of Multidisciplinary Research and Studies, 2023)
The purpose of this study was to analyze the effect of (1) green innovation on firm value, (2) carbon emission disclosure on firm value, (3) environmental costs on firm value, (4) type of industry in moderating green innovation on firm value, (5) type of industry in moderating carbon emission disclosure on company value, (6) type of industry in moderating environmental costs on company value. This research uses quantitative research methods. The sampling procedure in this study was based on a purposive sampling method, the population in this study totaled 52 companies with 260 data.This study uses secondary data, which is obtained from the internet through the official IDX website ( www.idx.co.id ) and the official website of each company. The data used are annual reports and sustainability reports published by each company that is the sample of this study. The statistical method used to test the hypothesis is by using the SPSS statistical application. The research results show that green innovation, carbon emission disclosure, and environmental costspositive effect on firm value. Whereas in the moderation effect in this study, the type of industry strengthens the effect of carbon emission disclosure on firm value, and the type of industry does not moderate the effect of green innovation and environmental costs on firm value.